Pemahaman Guru Muda Dayah Jamiah Al-Aziziyah Terhadap Implikasi Praktek Khitbah dan Praktek Pembatalan Khitbah: Studi Analisis menurut Fikih Syafi'iyah - Syarkawi, Syarkawi; Fazlon, Fazlon; Rahmalia, Rahmalia (el Buhuth: Borneo Journal of Islamic Studies, 2022)
Young Master's Understanding Dayah Jamiah Al- Aziziyah In this research, it is about the extent of understanding of the sermon, because before and after their request (the bride and groom) claimed to have felt that the bride was the right of the bride to do something unusual but the request was continued until the wedding. This research is contained by using field studies using a qualitative approach with data collection and information and monitoring methods. The method selected in the analysis of information is the reduction of information, information and gathering conclusions. The position of this research was carried out in Dayah Jamiah Al- Aziziyah. From the results of the study, it can be concluded that, in the application of the cancellation of the sermon, it leads to using the silence method until the person being applied for comes to say the cancellation of the sermon and returns the object that has been given from the applicant with the understanding and also the cancellation is from a natural perspective. Second, in Islamic thought, the application of this sermon is done on the basis of looking good from the field of wealth, religion, generation and good looks or beauty to want a good successor too. Then in the application of the cancellation of the sermon, it is carried out with a good method with the aim of maintaining brotherhood.